Organizational Crisis Management: Integrating Strategic Models, Human Factors, and Applied Frameworks - Malhooz, Zahra (Advances in Social Sciences Research Journal, 2025)
Crisis management has emerged as a crucial field in organizational studies due to the frequency, intensity, and unpredictability of crises in the modern era. Organizations today face complex and multi-dimensional threats, ranging from natural disasters to technological breakdowns, political instability, economic recessions, reputational scandals, and human-driven disruptions. Effective crisis management demands a comprehensive framework that integrates strategic foresight, operational readiness, and attention to human factors. This paper provides a descriptive synthesis of the crisis management literature, drawing from three primary perspectives: (1) strategic models and theoretical frameworks such as those developed by Parsons, Mitroff, Burnett, and Gonzalez-Herrero; (2) applied tools and systems, particularly risk management techniques and Geographic Information Systems (GIS); and (3) the human factors dimension, with a focus on the Treatment Assessment System (TAS) model, which highlights the roles of morale, loyalty, rumors, and behavioral shifts during crises. By combining these perspectives, this study argues that crisis management is not solely a technical process but a socio-technical phenomenon requiring strong leadership, transparent communication, and organizational adaptability. The discussion highlights the importance of early warning systems, simulation-based training, organizational learning, and post-crisis recovery planning. Ultimately, the integration of strategic models, technological tools, and human responses creates a holistic framework that enhances organizational resilience and transforms crises into opportunities for innovation and trust-building.